2015
DOI: 10.1002/jcb.25208
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Anti‐Apoptotic Effect of MicroRNA‐30b in Early Phase of Rat Myocardial Ischemia‐Reperfusion Injury Model

Abstract: This study aimed to investigate the effect of microRNA-30b (miR-30b) in rat myocardial ischemic-reperfusion (I/R) injury model. We randomly divided Sprague-Dawley (SD) rats (n = 80) into five groups: 1) control group; 2) miR-30b group; 3) sham-operated group; 4) I/R group, and 5) I/R+miR-30b group. Real-time quantitative polymerase chain reaction, immunohistochemical staining and Western blot analysis were conducted. TUNEL assay was employed for testing cardiomyocyte apoptosis. Our results showed that miR-30b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Interestingly, the expression levels of miR-101, miR-30b, miR-26b, and miR-18a were increased in miR-208a Tg mice. In previous works, miR-26b was shown to be anti-hypertrophic and prevented atrial fibrillation3839, miR-30b had anti-fibrotic and anti-apoptotic effects during IR injury4243, miR-18a prevented ECM remodeling40, and miR-101 prevented post infarct cardiac fibrosis and improved left ventricular compliance41. Taken together, these miRs could contribute to the results shown here.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Interestingly, the expression levels of miR-101, miR-30b, miR-26b, and miR-18a were increased in miR-208a Tg mice. In previous works, miR-26b was shown to be anti-hypertrophic and prevented atrial fibrillation3839, miR-30b had anti-fibrotic and anti-apoptotic effects during IR injury4243, miR-18a prevented ECM remodeling40, and miR-101 prevented post infarct cardiac fibrosis and improved left ventricular compliance41. Taken together, these miRs could contribute to the results shown here.…”
Section: Discussionsupporting
confidence: 69%
“…To investigate the possibility of miR-208a effects on other miRs, we focused on several key miRs that are down-regulated in heart failure and thus important for cardiac function383940414243. Interestingly, the expression levels for miR-30b, miR-26b, miR18a and miR-101 were increased in miR-208a transgenic hearts (Figure S10A–D).…”
Section: Resultsmentioning
confidence: 99%
“…Several miRNAs have been found to be dysregulated in response to myocardial I/R insults . Using an in vitro H/R injury model, we found that miR‐192‐5p was upregulated in H9c2 cells after H/R, suggesting its potential implication in this process.…”
Section: Discussionmentioning
confidence: 83%
“…proliferation and apoptosis of coronary artery endothelial cells via integrin subunit α 4, phospholipase γ 1 (48), caspase 3 (49) and Bcl-2 (50). Furthermore, myocardial miR-30b serves anti-apoptotic and protective roles during the pathological process of heart ischemia reperfusion (51,52). These studies suggest that miR-30b may be closely associated with the onset and development of heart disease in humans.…”
Section: Discussionmentioning
confidence: 86%